Pengabdian Kepada Masyarakat Berupa Pelatihan Penanganan Korban Sinkop Terhadap Keterampilan Murid SMA Kristen Petra Kota Kediri - Heru Suwardianto (Pelita Abdi Masyarakat, 2022)
Background: There are many incidents of fainting at school, especially during ceremonial activities or other out-of-school activities. The purpose of this study was to analyze the effect of training for handling fainting victims on the skills of Petra Christian High School students, Kediri City. Methods: The research design was pre-experimental. The population is all students of Petra Christian High School in Kediri City. The sample is 22 respondents with the sampling technique using Disproportionate Stratified Random Sampling. The independent variable is the effect of training in handling fainting victims. The dependent variable is the skill of handling fainting victims. Measuring instrument using Analog Range Scale (ARS 0-10): Skills. Statistical test using Wilcoxon test with <0.05. Results: The results showed that most of the respondents were male (54.5%), 15 years old (63.6%), class X (72.7%), science class (59.1%). The results of the study after the training showed that respondents had sufficient understanding (45.5%), had understood the purpose of the action (36.4%), had been able to carry out procedures (50%), had understood vigilance (45.5%), had can carry out evaluation measures (36.4%). Based on the results of statistical tests, it was found that all data groups had = 0.000 (ρ < ), which means that there is a significant difference before and after the purpose of the action (ρ = 0.000), the procedure of action (ρ = 0.000), action alertness (ρ = 0.000), and evaluation of the action (ρ = 0.000). Conclusion: Respondents experienced an increase in understanding of the goals, procedures, vigilance, and evaluation of actions after training in handling syncope victims.